2001
DOI: 10.1136/adc.85.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic adrenal insufficiency during inhaled corticosteroid treatment

Abstract: Symptomatic adrenal insuYciency, presenting as hypoglycaemia or poor weight gain, may occur on withdrawal of corticosteroid treatment but has not previously been reported during inhaled corticosteroid treatment. This case series illustrates the occurence of clinically significant adrenal insuYciency in asthmatic children while patients were on inhaled corticosteroid treatment and the unexpected modes of presentation. General practitioners and paediatricians need to be aware that this unusual but acute serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 30 publications
1
73
1
1
Order By: Relevance
“…The latter probably explains symptomatic adrenal insufficiency in children even on moderate doses of ICS [8]. Moreover, there are case reports of iatrogenic Cushing's syndrome in children even on conventional doses of ICS [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter probably explains symptomatic adrenal insufficiency in children even on moderate doses of ICS [8]. Moreover, there are case reports of iatrogenic Cushing's syndrome in children even on conventional doses of ICS [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The data from the current study of adrenal suppression in 20.8% of asthmatic children on mild and moderate doses of budesonide are in general agreement with the literature. The present authors do not know whether these children would present symptomatic adrenal insufficiency if they were treated with much larger doses of budesonide, such as children on large doses of fluticasone who reportedly experienced adrenal crisis [7][8][9][25][26][27]]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroid withdrawal could cause hypoglycemia and it was anecdotally reported that hypoglycemia can occur also during inhaled corticosteroid treatment (49). Only oral and not inhaled steroids were being administered in few (10) studies, which were performed at least 3 weeks from the last change in dosage.…”
Section: Discussionmentioning
confidence: 99%
“…oral corticosteroid Patel et al 2001 (30) Case series 4.5 to 10 years A higher than Hypoglycemia, little height gain, and limited of adrenal insufficiency (8 standard dose weight gain, together with altered serum cortisol, cases) treated with of an inhaled response to adrenocorticotropin stimulus inhaled corticosteroids corticosteroid and 24-h urinary cortisol metabolites was used in 1 case. Grebe et al 1997 (5) Controlled, observational 21 patients 4 to 8 years of 24-h urinary cortisol (p < 0.08), 1996 (29) paired 16+ years treatment with serum cortisol and tetracosactrin test beclomethasone were significantly (p < 0.05) lower than that of controls.…”
Section: Factors That Influence Systemic Absorptionmentioning
confidence: 99%